Heart rate variability of elite female rowers in preparation for and during the national selection regattas: a pilot study on the relation to on water performance - DeBlauw, J. A.; Stein, J. A.; Blackman, C.; Haas, M.; Makle, S.; Echevarria, I.; Edmons, R.; Ives, S. J. (Frontiers in Sports and Active Living, 2023)
Elite athletes require a delicate balance of physiological and psychological stress and recovery—essential for achieving optimal performance. Monitoring heart rate variability (HRV) provides a non-invasive estimation of both physiological and psychological stress levels, offering potentially valuable insights into health, performance, and adaptability. Previous studies, primarily conducted on male participants, have shown an association between HRV and performance in the context of rowing training. However, given the rigorous nature of rowing training, it is crucial to investigate HRV in elite rowers, particularly during the U.S. national selection regattas (NSR).